Pengaturan Penetapan Batas Pengelolaan Wilayah Laut Oleh Pemerintah Daerah Provinsi Maluku - Lawalata, Carmel Rafaela; Lekipiouw, Sherlock Halmes; Pattinasarany, Yohanes (Jurnal Saniri, 2024)
Article 27 and Article 28 of Law Number 23 of 2014 concerning Regional Government has given authority to provincial regions and provincial regions characterized by islands to manage natural resources in the sea in their territory. However, in its implementation, the Maluku Provincial Government has not yet established the Maluku Province Marine Area Management Boundary. Maluku Province is also a provincial area characterized by islands.The method used to analyze and discuss the problem is Normative Juridical. The problem studied in this research is the responsibility of the Regional Government of Maluku Province in determining the boundaries of the marine management area of Maluku Province and the legal consequences if Maluku Province does not determine its marine boundaries. The results showed that the responsibility of the Provincial Government in determining the boundaries of marine area management is regulated in Article 27 and Article 28 of Law Number 23 of 2014 concerning Regional Government. But in reality the authority has not been implemented by the Maluku Provincial Government. The legal consequences if the Maluku Provincial Government does not determine the boundaries of marine area management are the absence of legal certainty regarding the boundaries of marine area management as far as 12 (twelve) miles from Maluku Province and potentially regions bordering Maluku Province can issue permits to carry out management in marine areas that should belong to Maluku Province. sea area that should belong to Maluku Province.